2009
DOI: 10.2967/jnumed.109.067231
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG Small-Animal PET/CT Differentiates Trastuzumab-Responsive from Unresponsive Human Breast Cancer Xenografts in Athymic Mice

Abstract: Breast cancers (BCs) with high human epidermal growth factor receptor type 2 (HER2) expression are most likely to respond to trastuzumab; however, the mechanisms of action of trastuzumab are complex and there are no established biomarkers to accurately monitor treatment outcome in individual patients. Therefore, our aim was to determine, in human BC xenografts in athymic mice treated with trastuzumab, whether there were any changes in 18 F-FDG uptake that were associated with response to the drug and that coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
(51 reference statements)
3
22
0
Order By: Relevance
“…6A). These results are the first of its kind, but are consistent with an FDG-PET study of trastuzumab responsive and non-responsive breast cancer xenographs, demonstrating that HER2 inhibitors failed to reduce FDG uptake in those tumors whose growth was unaffected by trastuzumab [37]. Interestingly, the redox ratio of the trastuzumab and lapatinib resistant cells are different from the pre-treatment redox ratio value of responsive BT474 cells, p<0.001 (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…6A). These results are the first of its kind, but are consistent with an FDG-PET study of trastuzumab responsive and non-responsive breast cancer xenographs, demonstrating that HER2 inhibitors failed to reduce FDG uptake in those tumors whose growth was unaffected by trastuzumab [37]. Interestingly, the redox ratio of the trastuzumab and lapatinib resistant cells are different from the pre-treatment redox ratio value of responsive BT474 cells, p<0.001 (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…Generally, compared with pretreatment, responding tumors show decreased FDG uptake within a few days of starting chemotherapy. Two recent studies of human tumor xenografts [9,10] have produced conflicting findings regarding the effect of response to trastuzumab on FDG incorporation. McLarty et al [9] showed that treatment of MDA-MB-361 cells, which overexpress HER-2, exhibited a decline in FDG incorporation, whereas MDA-MB-231 cells, which do not overexpress HER-2, showed no change in FDG incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies of human tumor xenografts [9,10] have produced conflicting findings regarding the effect of response to trastuzumab on FDG incorporation. McLarty et al [9] showed that treatment of MDA-MB-361 cells, which overexpress HER-2, exhibited a decline in FDG incorporation, whereas MDA-MB-231 cells, which do not overexpress HER-2, showed no change in FDG incorporation. However, in the study by Shah et al [10], FDG incorporation by trastuzumab-treated MMTV/HER-2 and BT474 cells was found not to accompany response.…”
Section: Introductionmentioning
confidence: 99%
“…In the research setting, PET is increasingly being used to study early changes of biologic effects during and after anticancer treatment (7)(8)(9)(10). The noninvasive nature of PET allows multiple serial measurements without interfering with biologic processes within the tumor and might obviate more invasive procedures, such as biopsy.…”
mentioning
confidence: 99%